2020
DOI: 10.1167/tvst.9.5.20
|View full text |Cite
|
Sign up to set email alerts
|

Fundus Autofluorescence Lifetimes and Spectral Features of Soft Drusen and Hyperpigmentation in Age-Related Macular Degeneration

Abstract: lifetimes and spectral features of soft drusen and hyperpigmentation in age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 51 publications
4
32
1
Order By: Relevance
“…Although drusen can virtually be nonfluorescent, most of them emit fluorescence at shorter wavelength and with longer decay times than the RPE. Thus far, this study confirms in vivo FLIO results 6 and an earlier investigation performing spectrally resolved FLIM in the histology of one AMD and one control donor eye. 12 Relative to our previous study, 12 in histologic cross-sections sub-REP deposit autofluorescence is not overlaid by that of the RPE, and we had more donor material.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although drusen can virtually be nonfluorescent, most of them emit fluorescence at shorter wavelength and with longer decay times than the RPE. Thus far, this study confirms in vivo FLIO results 6 and an earlier investigation performing spectrally resolved FLIM in the histology of one AMD and one control donor eye. 12 Relative to our previous study, 12 in histologic cross-sections sub-REP deposit autofluorescence is not overlaid by that of the RPE, and we had more donor material.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent clinical study, we found one-third of soft drusen to be hyperfluorescent. 6 Investigating refractile drusen, Suzuki et al 31 found a transition from uniform hyper-FAF to a ring of hyper-FAF. Delori et al 29 explained the central hypofluorescence of drusen with a hyperfluorescent annulus by the thinning of the RPE on top of the druse with a translocation to its rim.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations